Dispatching plasma membrane cholesterol and Sonic Hedgehog dispatch: two sides of the same coin?. (1st November 2021) - Ehring, Kristina; Grobe, Kay
Abstract : Vertebrate and invertebrate Hedgehog (Hh) morphogens signal over short and long distances to direct cell fate decisions during development and to maintain tissue homeostasis after birth. One of the most important questions in Hh biology is how such Hh signaling to distant target cells is achieved, because all Hh proteins are secreted as dually lipidated proteins that firmly tether to the outer plasma membrane leaflet of their producing cells. There, Hhs multimerize into light microscopically visible storage platforms that recruit factors required for their regulated release. One such recruited release factor is the soluble glycoprotein Scube2 (Signal sequence, cubulin domain, epidermal-growth-factor-like protein 2), and maximal Scube2 function requires concomitant activity of the resistance-nodulation-division (RND) transporter Dispatched (Disp) at the plasma membrane of Hh-producing cells. Although recently published cryo-electron microscopy-derived structures suggest possible direct modes of Scube2/Disp-regulated Hh release, the mechanism of Disp-mediated Hh deployment is still not fully understood. In this review, we discuss suggested direct modes of Disp-dependent Hh deployment and relate them to the structural similarities between Disp and the related RND transporters Patched (Ptc) and Niemann-Pick type C protein 1. We then discuss open questions and perspectives that derive from these structural similarities, with particular focus on new findings that suggest shared small molecule transporter functions of Disp to deplete the plasma membrane of cholesterol and to modulate Hh release in an indirect manner.